Disability does not negatively impact linguistic visual-spatial processing for hearing adult learners of a signed language - Joyce, Taylor Renee; Quinto-Pozos, David; Singleton, Jenny L.; DiLeo, Michael (Frontiers in Communication, 2023)
The majority of adult learners of a signed language are hearing and have little to no experience with a signed language. Thus, they must simultaneously learn a specific language and how to communicate within the visual-gestural modality. Past studies have examined modality-unique drivers of acquisition within first and second signed language learners. In the former group, atypically developing signers have provided a unique axis—namely, disability—for analyzing the intersection of language, modality, and cognition. Here, we extend the question of how cognitive disabilities affect signed language acquisition to a novel audience: hearing, second language (L2) learners of a signed language. We ask whether disability status influences the processing of spatial scenes (perspective taking) and short sentences (phonological contrasts), two aspects of the learning of a signed language. For the methodology, we conducted a secondary, exploratory analysis of a data set including college-level American Sign Language (ASL) students. Participants completed an ASL phonological- discrimination task as well as non-linguistic and linguistic (ASL) versions of a perspective-taking task. Accuracy and response time measures for the tests were compared between a disability group with self-reported diagnoses (e.g., ADHD, learning disability) and a neurotypical group with no self-reported diagnoses. The results revealed that the disability group collectively had lower accuracy compared to the neurotypical group only on the non-linguistic perspective-taking task. Moreover, the group of students who specifically identified as having a learning disability performed worse than students who self-reported using other categories of disabilities affecting cognition. We interpret these findings as demonstrating, crucially, that the signed modality itself does not generally disadvantage disabled and/or neurodiverse learners, even those who may exhibit challenges in visuospatial processing. We recommend that signed language instructors specifically support and monitor students labeled with learning disabilities to ensure development of visual-spatial skills and processing in signed language.